OPPORTUNITIES FOR RUSSIA IN THE WTO TRADE DISPUTES SYSTEM - A. V. Larionov (Финансы: теория и практика)
This article reviews the problem of choosing an optimal strategy of behavior in the system of WTO trade dispute for Russia. The analysis is based on evaluating prospects of new WTO members. To conduct this analysis we examined the Chinese experience that has demonstrated that they prefer to use the system of «changeable measures» and an alternative tool - the prolongation of the trade dispute. Furthermore, it can be said that China preferred to accumulate experience on the first stage of membership. The analysis using game theory has demonstrated that Russia should actively participate in the WTO, not to disturb the WTO rules. This policy leads to the healthy competition and effective development in long-term. The econometric model has demonstrated that language and trade experience affect on the result of a trade dispute. Mainly the increase of the third parties leads to a Respondent losing the trade dispute.